Is Caravaggio a queer theologian? Paul's conversion on the way to Damascus - Menéndez Antuña, Luis (Critical research on religion, 2018)
Queer theology has not paid enough attention to queer sex, how queers understand sexual intimate relationships outside hetero/homonormative frameworks, and more importantly, what notions of relationality with Otherness undergird those experiences and practices. This contribution exemplifies a trajectory of visualization-a theoretically based approach to reading art-where the practices of barebacking and cruising in queer subcultures trigger a reading of Caravaggio's Conversion on the Way the Damascus that, in turn, reads the biblical text (Acts 9) in terms of radical hospitality to Otherness. Barebacking and cruising as sexual practices documented in queer subcultures offer a framework to understand Caravaggio's artwork as a theological source and as an interpretation of the biblical text.